2016
DOI: 10.4236/ojbm.2016.41004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Wood Prices: Analysis of Wood Retailers in Kumasi

Abstract: This paper investigates the determinants of wood pricing in Ghana. The purpose of this study is to assess the factors that influence the prices of wood product at the various wood markets and retailers in Kumasi which have large variety of wood and different categories of retailers in the industry. The study employs a survey design where respondents are conveniently selected. A semistructured questionnaire was designed to gather data from the respondents. STATA version 12.0 software and several sets of statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Timber price is one of the key elements in forest evaluation so the different prices of timber are unique to the factors of each timber tract: species, tree size, tree quality, volume of sale, distance to market, site accessibility, logging difficulty, market conditions etc. Kankam-Kwarteng et al (2016) reported the types of wood have greater influence in determining pricing of wood products since they consider some wood to be of better quality than others. Cost of transportation also plays a significant role in the pricing of the wood product.…”
Section: Evaluation Of Timber Valuesmentioning
confidence: 99%
“…Timber price is one of the key elements in forest evaluation so the different prices of timber are unique to the factors of each timber tract: species, tree size, tree quality, volume of sale, distance to market, site accessibility, logging difficulty, market conditions etc. Kankam-Kwarteng et al (2016) reported the types of wood have greater influence in determining pricing of wood products since they consider some wood to be of better quality than others. Cost of transportation also plays a significant role in the pricing of the wood product.…”
Section: Evaluation Of Timber Valuesmentioning
confidence: 99%